Facility and Community Results-Based Financing to Improve Maternal and Child Nutrition and Health in The Gambia. Issue 1 (1st January 2022) - Ferguson, Laura; Boudreaux, Chantelle; Cheyassin Phall, Modou; Jallow, Bakary; Fofana, Malang N.; Njie, Lamin; Ceesay, Abdou Aziz; Gibba, Catherine K.; Njie, Matty; Bittaye, Mustapha; Loum, Musa M.; Sankareh, Alhagie; et al.
ABSTRACT: In 2013, the Government of The Gambia implemented a novel results-based financing (RBF) intervention designed to improve maternal and child nutrition and health through a combination of community, facility and individual incentives. In a mixed-methods study, we used a randomized 2 × 2 study design to measure these interventions' impact on the uptake of priority maternal health services, hygiene and sanitation. Conditional cash transfers to individuals were bundled with facility results-based payments. Community groups received incentive payments conditional on completion of locally-designed health projects. Randomization occurred separately at health facility and community levels. Our model pools baseline, midline and endline exposure data to identify evidence of the interventions' impact in isolation or combination. Multivariable linear regression models were estimated. A qualitative study was embedded, with data thematically analyzed. We analyzed 5, 927 household surveys: 1, 939 baseline, 1, 951 midline, and 2, 037 endline. On average, community group interventions increased skilled deliveries by 11 percentage points, while the facility interventions package increased them by seven percentage points. No impact was found, either in the community group or facility intervention package arms on early ANC. The community group intervention led to 49, 43 and 48 percentage point increases in handwashing stations, soaps at station and water at station, respectively. No impact was found on improved sanitation facilities. The qualitative data help understand factors underlying these changes. No interaction was found between the community and facility interventions. Where demand-side barriers predominate and community governance structures exist, community group RBF interventions may be more effective than facility designs.